ANALISIS HUBUNGAN ANTARA BEBAN KERJA PERAWAT DENGAN STRES KERJA RUANG INTENSIF DI RSU MITRA MEDIKA AMPLAS MEDAN TAHUN 2020 - Sangkot Pandapotan (Jurnal Penelitian Kesmasy, 2022)
Hospital is an institution that provides medical care for various diseases or conditions of health problems. Hospitals are required to provide services of good quality and provide adequate facilities with qualified and professional human resources. Nurses are one of the most important resources for health services in hospitals. employment, 18% unfair wages, 22% working conditions, and 18% not included in decision making. This study shows the prevalence of mental emotional disorders in nurses is 17.7%. Research conducted at Mitra Medika Amplas General Hospital showed that 26.2% of nurses in the hospital were in a high risk group for work-related stress.10 The Indonesian National Nurses Association (PPNI) stated that even 50.9% of Indonesian nurses experienced stress due to overwork. This research is a type of quantitative research with a survey method, is cross sectional with a sample of 50 nurses. The research instrument was a questionnaire and data analysis was carried out by logistic regression test at a significance level of = 0.05. The results of the analysis in this study found a significant relationship between the workload of nurses and work stress in intensive care, pulse (p=0.002), nursing care (p=0.001), workload (p=0.002) and work stress in intensive nurses. The linear regression test stated that the most dominant variable influencing nursing care with (OR = 10.200) It is recommended to the hospital leadership to further improve welfare in dealing with work stress health by providing training related to work stress management, especially in the hospital environment in order to optimize the performance of nurses, especially in the nursing room. intensive.